Strategies For Coping Anxiety By The Students In Conducting Oral Presentations - fitriana, irta (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2023)
The purpose of this study is to cope students’ anxiety in conducting oral presentation in English for Interpersonal Communication course by applying strategies proposed by Kondo. The students taking part in the first semester in English of Interpersonal Communication course were chosen as the subject of this research. This research used descriptive qualitative method according to student’s experiences. Interviews were performed to collect data. The results show that there are several students show speech anxiety in delivering their oral presentation. Some students have also done some strategies such as concentration, positive thinking, preparation, and relaxation. Besides, the students have several practices every day to cope their anxiety.